Desain Sistem Pengukuran Lower Limb Joint Angles pada Kondisi Dinamik untuk FES - Rachmad Setiawan; Achmad Arifin; Fajar Budiman; Adi Soeprijanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
There are two gait parameters on FES used as feedback, namely gait phase and lower limb joint angles. Problems arise when the patient's motion is limited and the psychological factors of the patient are impaired due to the installation of sensors and the complicated wiring connected between the patient and the computer. This can hamper the rehabilitation process, thus a wearable and comfortable sensor system is required. This paper develops a measurement system of two gait parameters that are wearable and comfortable. The system is capable of accurately measuring two gait parameters, which are the lower limb joint angles of hip, knee, and ankle, using inertial sensors: accelerometers and gyroscopes, and gait phase parameter using Force Sensing Resistors (FSRs). The equations of the lower limb joint angles are also derived based on the acceleration vector of the accelerometer. Kalman filters are used to estimate the tilt angle of each lower limb segment based on the inertial sensor output. All processes are performed in real time by a 16-bit microcontroller, dsPIC4013. Measurement data is sent to the PC as a viewer and data storage wirelessly via Bluetooth module. In the test of dynamic subject, the gait parameters have been measured accurately. The required time to process and send all filtered sensor data is only 4.7 ms out of 10ms in maximum time sampling. This system can be further developed into wearable FES closed-loop system for gait restoration, with the addition of stimulus generator circuit and algorithm.